Clozapine-induced stuttering: an estimate of prevalence in the west of Ireland. (August 2015) - Murphy, Ruth; Gallagher, Anne; Sharma, Kapil; Ali, Tariq; Lewis, Elizabeth; Murray, Ivan; Hallahan, Brian
Objectives: Clozapine is the most effective treatment available for treatment-resistant schizophrenia; however, it is also associated with a large array of adverse effects that limits its tolerability. A number of previous case reports have noted an association between clozapine and stuttering, however the rate of this possible adverse effect is yet to be established. Methods: In this paper, we present six cases of patients treated with clozapine who developed stuttering. Results: Clozapine was associated with stuttering in 0.92% of individuals treated with clozapine in the region. Clozapine-induced stuttering was associated with an increase in treatment dose or with dose titration at initiation of clozapine in five individuals, with dose reduction or slower dose titration associated with a cessation of stuttering in these cases. Conclusions: This is the largest case series to date examining clozapine-induced stuttering and indicates that clozapine-induced stuttering is a relatively common adverse effect that can be managed by a slower titration of clozapine dosage or a modest reduction in dose in most cases.